Del revisionismo británico al postmodernismo: E. P. Thompson - Rodríguez Acevedo, José Manuel (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
In this paper we analise how the new postulates of the postmodern historiography are just a development of the positions already defended decades ago by the historians of the so known “British Marxism". This trend would have experienced a degenerative process, being E. P. Thompson a clear example of this aspect. If we analyse some of the main theoretical aspects of his work we can understand where are based the new idealistic conceptions which are wrongly presented as novel and rupturist.